Peran Orang Tua dan Guru dalam Mengembangkan Karakter Siswa Pada SD N 197 Rea Malempo - Fitri Fitri; Nur Syam; Ira Irviana (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
This study aims to find out what is the role of parents in shaping the character of students at SD Negeri 197 Rea Malempo, Mallawa District, Maros Regency, and to find out the teacher's role in developing the character of students at SD Negeri 198 Rea Malempo, Mallawa District, Maros Regency. The type of research used is field research that explores information that has one independent variable and one dependent variable. The independent variable is the parent and teacher variable and the dependent variable is developing student character in students. The population and research sample were fifth grade students at SD Negeri 197 Rea Malempo, consisting of 5, 5 parents and 8 teachers. Instruments and data collection are observation, questionnaires, interviews and documentation. Data analysis, data collection, data reduction, data presentation, verification and drawing conclusions, accuracy of checking data requirements. The research results obtained are: The role of the teacher is also very important in developing the character of students at SD Negeri 197 Rea Malempo because the teacher is someone who is imitated and as a student educator in the school environment.